Urbanization Challenges in Emerging Economies - Ranjan M.; Singh P.K.; Kumar V. (My University, 2025)
Majority of Indian population is dependent on groundwater to get drinking water. However, availability of groundwater in India has been reducing drastically due to urbanization, industrialization, and rapid growth of population. Nitrate is one of the most alarming chemical contaminant present in groundwater because its concentration in groundwater is increasing worldwide. Excess level of nitrate in drinking water leads to health hazard especially to infants and also affects the aquatic organisms. Sorptive properties of hydrous bismuth oxides for abatement of nitrate have been seriously examined and reported in many literatures. With the aim to further improvise the sorption potential of hydrous bismuth oxides (HBO), cations (Mn, Zr, Sn, Al, Ti) of higher charge has been added into the matrix of HBO. Addition of stannous into the matrix enhanced nitrate sorption potential of hydrous bismuth oxides. It was observed that pH of treated water was within the permissible limit. XRD analysis ensures that materials are crystalline in nature as they showed large and sharp peaks. © 2018 American Society of Civil Engineers.